2015
DOI: 10.1175/jtech-d-13-00185.1
|View full text |Cite
|
Sign up to set email alerts
|

General Application of the Relative Calibration Adjustment (RCA) Technique for Monitoring and Correcting Radar Reflectivity Calibration

Abstract: Accurate calibration of radar reflectivity is integral to quantitative radar measurements of precipitation and a myriad of other radar-based applications. A statistical method was developed that utilizes the probability distribution of clutter area reflectivity near a stationary, ground-based radar to provide near-real-time estimates of the relative calibration of reflectivity data. The relative calibration adjustment (RCA) method provides a valuable, automated near-real-time tool for maintaining consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 11 publications
(15 reference statements)
0
40
0
Order By: Relevance
“…The analysis has been restricted to 100 km range to make sure we were able to detect 0‐dBZ echo top heights at any included range. The existing 17‐year radar data set was calibrated using a combination of the Relative Calibration Adjustment technique (Wolff et al, ) and statistical comparisons with the NASA TRMM and Global Precipitation Measurement mission precipitation radars in space using the technique described in Warren et al (). Rainfall and cloud types were classified using the method described by Kumar, Jakob, Protat, May, and Davies ().…”
Section: Methodsmentioning
confidence: 99%
“…The analysis has been restricted to 100 km range to make sure we were able to detect 0‐dBZ echo top heights at any included range. The existing 17‐year radar data set was calibrated using a combination of the Relative Calibration Adjustment technique (Wolff et al, ) and statistical comparisons with the NASA TRMM and Global Precipitation Measurement mission precipitation radars in space using the technique described in Warren et al (). Rainfall and cloud types were classified using the method described by Kumar, Jakob, Protat, May, and Davies ().…”
Section: Methodsmentioning
confidence: 99%
“…GPM GV has established a world‐class inventory of precipitation instrumentation. Equipment developed and operated as part of this instrument suite include the NASA S‐band dual‐polarization (NPOL) radar (Wolff et al ., ), the Ku‐Ka band Dual‐frequency Dual‐Polarimetric Doppler Radar (D3R: Vega et al ., ), numerous Micro Rain Radars (MRR‐2; Peters et al ., ), Pluvio‐2 weighing gauges, dense networks of (multiple) tipping bucket rain‐gauges, snow imaging/measurement systems such as the Precipitation Imaging Package (PIP) (e.g. Newman et al ., ; Tiira et al ., ), and autonomously operating Parsivel and 2D Video Disdrometer (2DVD) networks (e.g.…”
Section: Ground Validation Activities and Contributions To The Gpm MImentioning
confidence: 99%
“…The error bars represent the estimated uncertainty. In the Sun calibration, the DRAO reference at 20:00 UTC, as reported in Wolff et al (2015), is subtracted from the observed solar power. The vertical blue lines divide the study period in three sectors as reported in the text.…”
Section: Discussionmentioning
confidence: 99%
“…The method of the ground clutter calibration is based on a clutter mask that is used to select clutter echoes that appear very frequently in the radar images. This is intended to minimize the possible contamination by meteorological echoes (Silberstein et al, 2008 andWolff et al, 2015). The radar volumes are processed by the hydrometeor classification algorithm (Bechini and Chandrasekar, 2015) to identify clutter and meteorological echoes.…”
Section: Ground Clutter Calibrationmentioning
confidence: 99%
See 1 more Smart Citation